2016
DOI: 10.1016/j.pt.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Current Threat of Triclabendazole Resistance in Fasciola hepatica

Abstract: Triclabendazole (TCBZ) is the only chemical that kills early immature and adult Fasciola hepatica (liver fluke) but widespread resistance to the drug greatly compromises fluke control in livestock and humans. The mode of action of TCBZ and mechanism(s) underlying parasite resistance to the drug are not known. Due to the high prevalence of TCBZ resistance (TCBZ-R), effective management of drug resistance is now critical for sustainable livestock production. Here, we discuss the current status of TCBZ-R in F. he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
193
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(197 citation statements)
references
References 87 publications
0
193
1
3
Order By: Relevance
“…Investigation of triclabendazole resistance in fluke in laboratories worldwide has resulted in the pursuit of a number of potential candidate genes and biological pathways (reviewed by Kelley et al, 2016). The precise loci and, therefore, genes involved are still to be defined but a genome-wide approach is currently underway to identify the major genetic determinant of triclabendazole resistance (Hodgkinson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of triclabendazole resistance in fluke in laboratories worldwide has resulted in the pursuit of a number of potential candidate genes and biological pathways (reviewed by Kelley et al, 2016). The precise loci and, therefore, genes involved are still to be defined but a genome-wide approach is currently underway to identify the major genetic determinant of triclabendazole resistance (Hodgkinson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance of F. hepatica to triclabendazole was first reported in sheep in Australia in 1995 (Overend and Bowen, 1995), and is now frequently reported across Europe and South America (Moll et al, 2000, Gaasenbeek et al, 2001, Álvarez-Sánchez et al, 2006, Mooney et al, 2009, Olaechea et al, 2011, Daniel et al, 2012, Ortiz et al, 2013). It is considered to be a substantial threat to the current and future control of F. hepatica (Kelley et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…As a result, TCBZ has become the drug of choice, particularly for treating acute fasciolosis in sheep, but this overreliance on TCBZ has inevitably resulted in the emergence of TCBZ‐resistance (TCBZ‐R) in liver fluke populations. The threat TCBZ‐R poses to the future control of liver fluke infections was the focus of a recent review which summarizes the number of cases reported worldwide, since the first report of TCBZ‐R in Australia in 1995 (Kelley et al., ; Overend & Bowen, ). To date, there are 20 peer‐reviewed reports of TCBZ‐R on sheep farms within Europe (Table ), plus a number of anecdotal reports of resistance, which raises the question how prevalent is TCBZ‐R in Europe?…”
Section: Anthelmintic Resistancementioning
confidence: 99%
“…hepatica [10]. Triclabendazole (TCBZ) is the drug of choice since its effective against juveniles and adult liver flukes, but resistance to this benzimidazole has emerged in livestock in different countries [11]. There have been recent reports of human fascioliasis refractive to TCBZ treatment in Peru and Chile [12, 13], highlighting a need for alternative drugs and treatments.…”
Section: Introductionmentioning
confidence: 99%